Design and Development of a technique for Hidden data in Watermark Image using Steganography: An Exploration - Verma, Upendra; Rambola, R.K; Meshram, Pratiksha (International Journal of Computer Sciences and Engineering, 2025)
The improvement of sight and sound and web takes into consideration wide conveyance of computerized media information. It turns out to be significantly less demanding to alter, adjust and copy advanced data. In extra, advanced report is likewise simple to duplicate and appropriate, along these lines it might confront numerous dangers. It ended up plainly important to locate a suitable security because of the centrality, exactness and affectability of the data. Besides, there is no formal technique to be taken after to find shrouded information. In this paper, we proposed an approach amongst Steganography and Watermarking. In this paper, another data concealing framework is introduced. The point of the proposed framework is to shroud data (information document) inside watermark picture. This paper covers three fundamental standards of security: Confidentiality, Integrity and Authentication (CIA).